Betrayal of Gloria and Other Stories - Chukwu, Blessing (Literamed Publications Ltd, 2003)
This book is an anthology of short stories that catalogues the various ups and downs in the day to day life experiences of human beings$1! =s
Keywords: Juvenile Fiction